2021
DOI: 10.1146/annurev-statistics-042720-104044
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Applications in Educational Measurement

Abstract: Educational measurement assigns numbers to individuals based on observed data to represent individuals' educational properties such as abilities, aptitudes, achievements, progress, and performance. The current review introduces a selection of statistical applications to educational measurement, ranging from classical statistical theory (e.g., Pearson correlation and the Mantel–Haenszel test) to more sophisticated models (e.g., latent variable, survival, and mixture modeling) and statistical and machine learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…A non‐sequential implementation can be found in Chalmers and Ng ( 2017 ). Finally, while the proposed method is aimed at detecting item compromise occurring in large‐scale continuous tests, as remote learning and testing become increasingly relevant, future studies can also explore the adaptation of the methods here to address the item compromise issues in formative classroom assessments (Chang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A non‐sequential implementation can be found in Chalmers and Ng ( 2017 ). Finally, while the proposed method is aimed at detecting item compromise occurring in large‐scale continuous tests, as remote learning and testing become increasingly relevant, future studies can also explore the adaptation of the methods here to address the item compromise issues in formative classroom assessments (Chang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…CDMs are a class of psychometric models that combine modern statistical methods with cognitive theories and therefore produce feedbacks that reflect the cognitive and psychological characteristics of the subjects (Templin and Henson, 2010;Wu et al, 2020Wu et al, , 2021c. It holds great promise in providing fine-grained feedback (Leighton and Gierl, 2007;Templin and Bradshaw, 2014;Chang et al, 2021). For diagnostic purposes, CDMs could identify multiple criterion-referenced interpretations for numerous attributes in solving the test items.…”
Section: Assessments Of Cognitive Diagnostic Models Via Large-scale Datasetsmentioning
confidence: 99%
“…This research identified several common reading attributes crucial for successful reading and supported the use of CDMs as a promising approach that pinpoints students’ weaknesses and strengths in mastering these reading attributes (Li et al, 2021). However, the application of such fine-grained feedback is scarce as it requires students to answer a static, time-consuming, or less accurate test paper (Chang et al, 2021). Formative assessment of children’s reading ability and subskills is essential and ongoing throughout their primary school years (Carlson et al, 2014), and therefore, it is worthy of exploring a more accurate and efficient way.…”
Section: Introductionmentioning
confidence: 99%